Identification of the Main Aspects of Innovation Management and the Problems Arising from their Misunderstanding - Lendel, Viliam; Hittmar, Stefan; Sroka, Wlodzimierz; Siantova, Eva (Communications - Scientific letters of the University of Zilina, 2016)
Goal of the article is to identify main aspects of innovation management using detailed analysis of available scientific literature together with outcomes of performed empirical research. With the identified main aspects, we were able to identify problematic areas related to the use of innovation management and to propose a number of recommendations in order to correct these issues. The article thus brings to managers a handy tool in a form of a set of recommendations (instructions) that are meant to support problem-free use of innovation management within a company.